1999
DOI: 10.1034/j.1399-6576.1999.430510.x
|View full text |Cite
|
Sign up to set email alerts
|

EEG bispectral index monitoring in sevoflurane or propofol anaesthesia: analysis of direct costs and immediate recovery

Abstract: BIS monitoring decreased the consumption of both propofol and sevoflurane and hastened the immediate recovery after propofol anaesthesia. Detailed cost analysis showed that the monitoring increased direct costs of anaesthesia treatment in these patients, mainly due to the price of special EEG electrodes used for relatively short anaesthesias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
2
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(73 citation statements)
references
References 6 publications
8
57
2
6
Order By: Relevance
“…Alkire et al showed that time to extubation was significantly shorter under BIS monitoring than under routine care [37]. Similar results were found by the following studies [35,39,[42][43][44]. Our results are consistent with the study of Sadaqa et al that showed no significant difference in time to extubation of BIS monitoring and routine care groups in a randomized control study using Bispectral index monitoring during cardiopulmonary bypass surgery [45].…”
Section: Journal Of Biomedical Sciences Issn 2254-609xsupporting
confidence: 92%
See 1 more Smart Citation
“…Alkire et al showed that time to extubation was significantly shorter under BIS monitoring than under routine care [37]. Similar results were found by the following studies [35,39,[42][43][44]. Our results are consistent with the study of Sadaqa et al that showed no significant difference in time to extubation of BIS monitoring and routine care groups in a randomized control study using Bispectral index monitoring during cardiopulmonary bypass surgery [45].…”
Section: Journal Of Biomedical Sciences Issn 2254-609xsupporting
confidence: 92%
“…Yili-Hankala et al compared propofol and sevoflurane under BIS and routine care protocols and found less consumption of both propofol and sevoflurane in the BIS monitored group. These studies show that BIS monitoring is helpful for lowering the consumption of propofol during anesthesia [39] which is not the case in our study. Friedberg et al found that BIS index monitoring decreased propofol consumption by 20% as compared to routine care [40].…”
Section: Anesthetic Drugs Consumptioncontrasting
confidence: 64%
“…Wie oben bereits für den BIS-Monitor beschrieben, stellen verkürzte Aufwachzeiten einen weiteren Vorteil der Überwachung des Narkose-EEG dar [1,3,4,6,16]. Dies konnte auch in der vorliegenden Untersuchung für den Narcotrend-Monitor bestätigt werden: Durch Ansteuerung der Stufen D oder E war eine signifikante Reduktion der Aufwachzeiten im Vergleich zur Patientengruppe mit klinischer Anästhesiesteue-rung möglich.Vor dem Hintergrund der Tatsache, dass die in der vorliegenden Untersuchung angesteuerten Narcotrend-Stufen D und E eine durchaus unterschiedliche "Narkosetiefe" repräsen-tieren [7], erschien eine getrennte Analyse der Aufwachzeiten sinnvoll.…”
Section: Einfluss Des Verwendeten Opioidsunclassified
“…Sevofluran tüketimin-de tespit edilen % 25,3'lük azalma BİS ile anestezi derinliğinin takibinde tüketilen ilaç miktarlarının azaldığını gösteren daha önce yapılmış çalışmaları destekler niteliktedir. (6,(18)(19)(20)(21) Ganidağlı ve ark. (22) ASA I-II 14-65 yaş arası 70 hasta üzerinde yaptıkları çalışmada hastaların anestezi derinliğinin belirlenmesinde BİS monitörizasyonu yapılanlar ve hemodinamik parametrelere göre takip edilenler olmak üzere 2 gruba ayırmıştır.…”
Section: Discussionunclassified